Development Strategy for Heritage Tourism Areas in Bandung City - Raja Kamal Faried; I Made Sendra; Nyoman Ariana (International Journal of Education, Vocational and Social Science, 2025)
This study explores the development strategy for Bandung's heritage tourism area, emphasizing its historical and cultural significance. The research identifies strategies to enhance heritage tourism as an attraction, evaluates the role of pentahelix stakeholders, and analyzes improvements for sustainable development. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation. Key theoretical frameworks include heritage tourism, development strategies, nostalgic tourism, and the old town concept, with SWOT analysis employed for data interpretation. Findings reveal that the Bandung Heritage Tourism Area, rich in historical and cultural assets, serves as a major tourist attraction. Primary stakeholders include the government and local communities, while academics, media, and businesses act as secondary stakeholders. Development strategies focus on utilizing historical assets, improving amenities, and enhancing security to ensure visitor safety and comfort. Promotional efforts are also critical in attracting tourists. Recommendations highlight the importance of active stakeholder collaboration to sustain and promote the heritage tourism area, ensuring its long-term viability and appeal.